The Priestly Gift of Mishnah A Study of Tractate Terumot - Avery-Peck, Alan J. (Brown Judaic Studies, 2020)
This study systematically analyzes Tractate Terumot (heave-offerings) in the Mishnah and its corresponding document, the Tosefta. It provides a new translation of and commentary on Terumot and considers the shape and message of the tractate as a whole.